Penerapan Kaidah Nun Sukun pada Pembelajaran Tahsin - Tiara Tiara; Dahniar Dahniar; Elviani Elviani (Jurnal Manajemen dan Pendidikan Agama Islam, 2026)
This study aims to analyze the implementation of the rules of nun sukun in Qur’anic tahsin learning and to evaluate the effectiveness of the instructional methods used in improving students’ ability to recite the Qur’an fluently and accurately. The rules of nun sukun, which include izhar, idgham, iqlab, and ikhfa, are essential components of tajwid that must be understood and applied correctly to ensure proper Qur’anic recitation. This research employed a qualitative approach with a descriptive-analytical design. The participants were students enrolled in a Qur’anic tahsin program at an Islamic educational institution who experienced difficulties in applying the rules of nun sukun. Data were collected through observation, interviews, and documentation and were analyzed using descriptive qualitative techniques. The findings revealed that the most frequent errors occurred in the application of izhar and ikhfa, while mistakes in idgham and iqlab were also commonly found. The primary factors contributing to these difficulties were the dominance of theory-based instruction and the limited opportunities for structured and continuous practical exercises. The study further found that learning methods emphasizing direct practice, repeated exposure to Qur’anic verses, teacher modeling, and individualized feedback were more effective in enhancing students’ understanding and application of the rules of nun sukun. The research concludes that systematic and practice-oriented instructional strategies play a significant role in improving the quality of Qur’anic recitation. The results are expected to serve as a reference for tahsin teachers and Islamic educational institutions in developing more effective and practical tajwid teaching methods to improve students’ recitation skills.